Acinetobacter baumannii and Cefiderocol, between Cidality and Adaptability - Stefano Stracquadanio; Carmelo Bonomo; Andrea Marino; Dafne Bongiorno; Grete Francesca Privitera; Dalida Angela Bivona; Alessia Mirabile; Paolo Giuseppe Bonacci; Stefania Stefani (Microbiology Spectrum, 2022)
ABSTRACT Among the bacterial species included in the ESKAPE group, Acinetobacter baumannii is of great interest due to its intrinsic and acquired resistance to many antibiotics and its ability to infect different body regions. Cefiderocol (FDC) is a novel cephalosporin that is active against Gram-negative bacteria, with promising efficacy for A. baumannii infections, but some studies have reported therapeutic failures even in the presence of susceptible strains. This study aims to investigate the interactions between FDC and 10 A. baumannii strains with different susceptibilities to this drug. We confirmed diverse susceptibility profiles, with resistance values close to the EUCAST-proposed breakpoints. The minimal bactericidal concentration (MBC)/MIC ratios demonstrated bactericidal activity of the drug, with ratio values of ≤4 for all of the strains except ATCC 19606; however, bacterial regrowth was evident after exposure to FDC, as were changes in the shapes of colonies and bacterial cells. A switch to a nonsusceptible phenotype in the presence of high FDC concentrations was found in 1 strain as an adaptation mechanism implemented to overcome the cidal activity of this antibiotic, which was confirmed by the presence of heteroresistant, unstable subpopulations in 8/10 samples. Genomic analyses revealed the presence of mutations in penicillin-binding protein 3 (PBP3) and TonB3 that were shared by all of the strains regardless of their resistance phenotype. Because our isolates harbored β-lactamase genes, β-lactamase inhibitors showed the ability to restore the antimicrobial activity of FDC despite the different nonsusceptibility levels of the tested strains. These in vitro results support the concept of using combination therapy to eliminate drug-adapted subpopulations and regain full FDC activity in this difficult-to-treat species. IMPORTANCE This work demonstrates the underrated presence of Acinetobacter baumannii heteroresistant subpopulations after exposure of A. baumannii strains to FDC and its instability. Both A. baumannii and FDC are of great interest for the scientific community, as well as for clinicians; the former represents a major threat to public health due to its resistance to antibiotics, with related costs of prolonged hospitalization, and the latter is a novel, promising cephalosporin currently under the magnifying glass.